PKM. PELATIHAN PENULISAN KARYA TULIS ILMIAH DAN PUBLIKASI ILMIAH DI SDN 3 PENATIH - Ida Ayu Agung Ekasriadi; I Komang Sukendra; Putu Dessy Fridayanthi; Gusti Ayu Made Puspawati (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Scientific publications carried out by teachers are basically a manifestation of teacher professionalism. The aim of this service is to find a solution to the problem of teachers' lack of knowledge in writing scientific papers and scientific publications in the form of classroom action research. This problem can be overcome by increasing capacity through learning with outreach through two approaches, namely training and mentoring. In general, the implementation of PKM at SDN 3 Penatih has run smoothly according to the predetermined schedule. In implementing the 1st and 2nd stages of PKM socialization, much progress has been achieved. In writing scientific papers, conveying scientific information to the general public requires a writing technique that meets scientific rules and ethics in accordance with scientific standards. From the results of the mentoring, the teacher's skills in writing rich scientific writing increased. Scientific writing training discusses the urgency of writing, the systematics of writing papers, and the systematics of making research reports followed by writing articles for publication in nationally accredited scientific journals. The material was delivered by lecturers from the PKM Team at PGRI Mahadewa Indonesia University. The PTK results will later be presented as a condition for promotion for teachers to higher levels.